SHARIA RURAL BANK’S PERFORMANCE: CAPITAL, FINTECH, FUNDS AND CREDIT RISK - Rahmadanti, Akmila Aning; Nawirah, Nawirah (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 11 No 1 (2025): The 11th International Conference of Islamic Economics and Business (ICONIES 2025), 2025)
This research examines the interrelationship among capital adequacy ratio, financial technology, and third-party funds on financial performance, focusing on the moderating role of credit risk. The sample consisted of twenty-five Islamic Rural Banks in Indonesia, selected through purposive sampling from those listed in the Financial Services Authority (OJK) from 2019 to 2024 and cooperating with PT Komunal Indonesia. The research employed panel data regression analysis conducted with E-Views 12 software, with quarterly financial statements as the primary data source. The findings reveal that while the capital adequacy ratio partially does not determine financial performance, it significantly impacts when credit risk is considered a moderator. Additionally, financial technology partially affects financial performance, and credit risk enhances the relationship between financial technology and performance. Conversely, third-party funds did not significantly affect financial performance, and credit risk did not moderate the two variables. According to the study's findings, Sharia Rural Bank management should be able to make informed decisions regarding business strategy and the utilization of productive assets by considering the evolving technological landscape to maintain public trust.